2020
DOI: 10.1111/jrh.12483
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Health Care Access in Rural Latino Communities: An Innovative Model in the Eastern Coachella Valley

Abstract: Acknowledgments: We thank Maria "Conchita" Pozar for her engagement of the community, the promotoras who built trust with participants, and the volunteer students and health care providers who are committed to serving rural patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Provision of services within local communities, as well as offering extended hours, are also organizational approaches found to improve access to care (139)(140)(141). In addition to helping services to be available from a logistical standpoint, organizations can foster an environment in which providers have opportunities to learn about cultural responsiveness, sources of resilience, and best practices with Latino communities (111,125,129,140).…”
Section: Discussionmentioning
confidence: 99%
“…Provision of services within local communities, as well as offering extended hours, are also organizational approaches found to improve access to care (139)(140)(141). In addition to helping services to be available from a logistical standpoint, organizations can foster an environment in which providers have opportunities to learn about cultural responsiveness, sources of resilience, and best practices with Latino communities (111,125,129,140).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on SRCs have analyzed the quality of patient care, including patient satisfaction and clinical outcomes [11][12][13][14]. Similarly, prior studies have investigated how effectively SRCs address access to care, cost of care, and other socioeconomic barriers to quality health care [15][16][17][18][19][20]. Smith et al found that clinical outcomes for diabetic patients treated at the University of California San Diego Student-Run Free Clinic met or exceeded standards compared to other studies [12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported barriers to accessing health care among farmworkers. Many farmworkers live and work in rural areas, which present unique challenges in reaching care, such as difficulty attaining transportation to and from appointments [8][9][10]. Farmworkers, specifically those working in certain areas or crops are often immigrants, or have family members who are immigrants, and have reported fear of immigration enforcement as a barrier to accessing health care [8][9][10].…”
Section: Introductionmentioning
confidence: 99%